ALBRIDIUWM AND THEIR POLITICAL AND MILITARY ROLE AT THE END OF THE SECOND ABBASID ERA IN THE SOUTHERN IRAQ - Asaad, Abdulbari; Yousif , Tawfeeq (Humanities Journal of University of Zakho, 2025)
The exact origin of the Albridiuwm family is not known, which appeared on the scene in the last years of the second Abbasid era. First, they did some minor careers in southern Iraq but did not rise to the level of becoming an affected force. However, due to the chaos that the Abbasid state was exposed to at the end of the second era, the emergence of the Albridiyn was a natural result. Because their goal was only to obtain the personal privilege of their princes, they did not have political program, and what they did was only to take power and collect money at a time when there was no power controlling the situation in the Abbasid state. Because the Turkish leaders and ministers contributed to the creation of that chaos, this resulted in the growing ambition of the Baridi family. Their relations were fluctuating, whether with the Turkish leaders and ministers, the Buyids, the Qarmatians, or even with the Abbasid caliphs. The relationships with those personalities and powers that existed at the time were only based on mutual consent and interest. As soon as it ends, their princes will become hostile with those who stand against their aspirations for power and money. As soon as the Buyid forces entered Iraq, their movements shrank and were confined to the southern regions of Iraq. In the end, when the Buyid forces got stronger, they got rid of the Albridiuwm, and things stabilized, as if their end was easy and simple.